Transparansi Keuangan Masjid di Era Digital: Mewujudkan Tata Kelola Amanah dan Bebas Fraud - Suharsono, Riyanto Setiawan; Sudarmanto, Eko; Mahdi, Fadilla Muhammad; Mubarok, Ahmad Zaki; Ridwan, Mohammad (Jurnal Ilmiah Ekonomi Islam, 2025)
Transparent and trustworthy financial management in mosques is a fundamental pillar for maintaining institutional integrity and preventing financial fraud. This article explores the importance of implementing mosque accounting practices that are accountable and aligned with good financial governance principles to enhance public and congregational trust. Using a descriptive-qualitative approach and literature review, the study identifies that many mosques still manage finances in a disorganized and non-transparent manner, with limited oversight. Such conditions increase the risk of fund misappropriation. To address this issue, the article proposes strategies such as adopting digital bookkeeping systems, providing basic accounting training for mosque administrators, and ensuring regular and publicly accessible financial reporting. The application of transparency, congregational participation, and periodic audits are key components in establishing a professional and trustworthy accounting system for mosques. The study concludes that structured financial governance, grounded in Islamic values, is an effective approach to preventing fraud and strengthening the financial accountability of mosque institutions.